2015
DOI: 10.1007/s00420-015-1061-y
|View full text |Cite
|
Sign up to set email alerts
|

Return to work from long-term sick leave: a six-year prospective study of the importance of adjustment latitudes at work and home

Abstract: This study highlights the importance of opportunities for adjustment latitude at work to increase work ability and return to work among female human service workers who have been on long-term sick leave. The results support push and pull theories for individual decision-making on return to work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…Earlier prospective studies have found a strong relationship between opportunities to choose work tasks and employees’ sustainable health, as workload variation and being able to take short breaks when needed provide opportunities for recovery. This is important the ability to sustain work despite musculoskeletal pain or stress (Dellve, Fallman, & Ahlstrom, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier prospective studies have found a strong relationship between opportunities to choose work tasks and employees’ sustainable health, as workload variation and being able to take short breaks when needed provide opportunities for recovery. This is important the ability to sustain work despite musculoskeletal pain or stress (Dellve, Fallman, & Ahlstrom, ).…”
Section: Discussionmentioning
confidence: 99%
“…This is important the ability to sustain work despite musculoskeletal pain or stress (Dellve, Fallman, & Ahlstrom, 2016).…”
Section: Standardization Flow and Work Characteristicsmentioning
confidence: 99%
“…In this respect, a structured, systematic occupational health and safety management system, with activities and goals from health-promotive, preventive, and rehabilitation perspectives, is important for the prevention of employees' work-related injuries and diseases. These and other structural empowerment conditions are designed to decrease illness, but also increase influence and control, as well as delegate power and authority (i.e., enabling bureaucracy), of importance for both work satisfaction [10], and work attendance [56,57]. Likewise, can organizational preconditions support managers to better perform complex daily work practices in complex human service organizations?…”
Section: The Modelmentioning
confidence: 99%
“…Having flextime has been shown to have an impact on job satisfaction [ 8 ] and a positive effect on productivity [ 10 ], although previously reported results were not specific for young women. Adult women with poor health and the opportunity to adjust their worktime were prospectively associated with increased work ability and return to work [ 28 ]; however, a large part of that study’s sample had poor work ability at baseline, which casts doubt on the appropriateness of a direct comparison with results of the current study. As no other recovery opportunities at work were found in the present study to be associated with excellent work ability among young women, other external factors such as duration and/or quality of sleep and/or relaxation between work-days may, in our opinion, be more important to their maintaining excellent work ability.…”
Section: Discussionmentioning
confidence: 94%